Pendidikan Kesehatan Jigsaw dan Make a Match dalam Mencegah Fluor Albus pada Remaja Pondok Pesantren - Laily Bestari Putri; Esti Yunitasari; Praba Diyan Rachmawati (Pediomaternal Nursing Journal, 2019)
Introduction: : Fluor albus is experienced by adolescents which is equal to 75%, especially adolescents in islamic boarding schools because less of information about their reproductive health. Promotive and preventive efforts need to be carried out by conducting appropriate health education, namely the Jigsaw and Make a Match methods about personal hygiene. This study aims to determine the effect of Jigsaw and Make a Match health education methods to prevent fluor albus.Methods: This study used the Quasy Experiment design which was divided into 3 groups (Jigsaw, Make a Match, and control). The number of samples used was 108 of 1,856 students. The sampling technique uses Simple Random Sampling by randomizing Nomer Induk Siswa Nasional. Independent variables are Jigsaw and Make a Match health education methods. Dependent variable is fluor albus prevention behavior. The instruments used were 3 questionnaires and 1 observation sheet that had been tested for validity and reliability with results in the knowledge category r = 0.935, attitude categories r = 0.936, and actions r = 0.921. Data analysis using the Wilcoxon Signed Rank Test and Kruskal Wallis test.Results: Health education using the Jigsaw method has a greater result than the Make a Match method in increasing fluor albus prevention behavior with the results of Willcoxon analysis p = 0.0000 and the mean in the Kruskall Wallis analysis the knowledge category is 84.35, attitude is 82.03, action is 79.49, and action observations amounted to 79.46.Conclusion: Health education using Jigsaw and Make a Match methods is used to develop health promotion nursing interventions to improve fluor albus prevention behavior.